Shallow anatomy of hydrothermal systems controlled by the Liquiñe-Ofqui Fault System and the Andean Transverse Faults: Geophysical imaging of fluid pathways and practical implications for geothermal exploration. (September 2022) - Pérez-Estay, N.; Molina-Piernas, E.; Roquer, T.; Aravena, D.; Araya Vargas, J.; Morata, D.; Arancibia, G.; Valdenegro, P.; García, K.; Elizalde, D.
Highlights: We combined ERT, nakamura's method, and geological mapping to localize thermal water. Hotspring's thermal water is fed by vertical conduits aligned with local faults. Significant amount of hot water is dispersed in horizontal bodies within sediments. The hydrothermal systems are twice longer within sediments than the hotspring area. We present a model of the shallow anatomy of fault-controlled hydrothermal systems. Abstract: We combined geoelectric and seismic ambient noise methods to image the shallow depth (<30 m) distribution of thermal waters in two fault-controlled hydrothermal systems located in southern Chile. The bedrock depth was constrained with seismics, while hotsprings and mapped faults were imaged by low-electrical-resistivity domains (<160 Ωm) defined with electrical resistivity tomographies (ERT). The distribution and shape of low-resistivity-domains suggest that thermal fluids follow complex pathways, including deep vertical conduits hosted in fractured rock and shallow horizontal bodies hosted in sediments. These results indicate that the studied hydrothermal systems are at least twice longer within the sediments than the superficial area covered by hotsprings. Graphical abstract: Image, graphical abstract